(3GdVjGA GdeSJHjf HcQGeGJ GdTjN eMeO GdaGVd Hf GdTjN eMeO GdCejfs - (3eMeO aGVd Hf GdMHjH GdjYbhHjs ((3GdTjM eGA GdYjfjf s)
(3ChdgG (B:s
(3hHYO , Efg eGRGd HjNWQ HHGdi Cf CVY cJGHG eNJUQkG CPcQ ajg HYV cQGeGJ TjNfG GdTjN eMeO GdaGVd hefGbHg GdTQjaI hGdBf CTQY Ef TGA Gddg aj gPG GdcJGH s
(3BNQgG (B:s
(3Udi Gddg Ydi SjOfG eMeO NGJe GdfHjjf hEeGe GdoeQSdjf hYdi ENhGfg GdfHjjf hBNQ OYhGfG Cf GdMeO ddg QH GdYGdejf s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B267 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(1067 (3O(B) s
Keywords: (3GdJGQjNs